Idosos apresentam alteração do padrão de movimento de pelve e de tronco durante a marcha? uma revisão sistemática com meta-análise e recomendações grade - Ana Carolina Cury (2020)
Several factors affect the gait efficiency of older adults, such as cognitive, sensory and biomechanical aspects. Among the biomechanical factors, the reduction in the range of motion (ROM) of the pelvis and trunk segments has been associated with lower gait speed, shorter stride length and greater susceptibility to falls. The purpose of this dissertation was to review the studies that compared the movement of the pelvis and trunk during gait between adults and older adults. The electronic search was performed in the MEDLINE, EMBASE and Cinahl databases, from inception until May, 2020. Studies were included in the review if they compared the angular displacement of the trunk and/or pelvis during gait between adults and older adults. Studies with participants with any health condition that could influence gait were excluded. The following data were extracted: gait speed, walking surface and range of motion (ROM) of the trunk and pelvis during gait in the three planes of movement. Meta-analyzes were calculated for three different ranges of gait speed using the random effects model and summarized statistically using the standardized mean difference (SMD). The GRADE system was applied to determine the strength of the evidence. The search identified 1414 articles (excluding duplicates). After screening, twelve studies were included for quantitative review. The results showed evidence of moderate quality that the elderly offer a lower ROM of pelvic rotation during walking at self-transmitted speed (SMD= -0.90 [-1.35, -0.45]) and a lower ROM of pelvic rotation during walking. walking at fast speed (SMD = -1.55 [-3.43, -0.33]). In addition, there was low-quality evidence that the older adults have a smaller ROM of trunk rotation during walking at rapid speed (SMD= -0.63 [-1.23, -0.03]). There was no difference between adults and older adults in ROM of pelvic and trunk movements in the sagittal and frontal regardless of walking speed. Older adults walk with smaller pelvic rotation ROM at self-selected and fast speeds, and lower trunk rotation ROM during fast speed. The quality of the evidence varied from low to high.